Longitudinal Patterns of Food Procurement Over the Course of the COVID-19 Pandemic: Findings From a Canadian Online Household Survey - Daiva E. Nielsen; Katherine Labonté; Irem Karamanoglu; Hannah Yang Han; Mandana Tavanaei; Paul-Guy Duhamel; Luis B. Agellon; Catherine Paquet; Laurette Dube (Frontiers Media S.A., 2022)
IntroductionConsumer food procurement during the COVID-19 pandemic has been understudied. This investigation aimed to longitudinally evaluate food procurement patterns, concern of virus exposure in grocery retailers, and food access challenges over the pandemic among a sample of households in Quebec, Canada.MethodsOnline surveys were collected at three time points of the pandemic: first wave in spring 2020 (lockdown period), summer 2020 (deconfinement period), and second wave in winter 2021 (curfew period). Respondents were the household's primary grocery shopper (n = 491). Non-parametric tests and multivariable logistic regression were conducted to compare responses over time and to evaluate characteristics of respondents who regularly used no-contact grocery methods (store pick-up or home delivery).ResultsFrequency of in-store grocery shopping was lowest during the lockdown (once per week or less), and significantly increased over time to resemble pre-pandemic frequency. Concern of virus exposure in grocery retailers and disinfection/discarding of food packaging was highest during the lockdown, but significantly decreased over time. At all time points, use of public transit, walking or cycling for grocery shopping was associated with regular use of no-contact grocery methods (curfew odds ratio (OR): 3.13 (95% confidence interval 1.60, 6.14). Age (60 years+) was associated with regular use during the lockdown [OR: 2.27 (1.13, 4.59)].ConclusionAmong our sample, frequency of in-store grocery shopping was lowest and concern of virus exposure in stores was highest during the lockdown period. No-contact grocery use was associated with transportation mode and potentially with personal risk perception (age).